The Resonance and Articulation of the Roman Moral Imagination in the Historical Thought of Sallust and Plutarch - Philips, James Patrick (East Carolina University)
Within the Roman historical imagination from Polybius forward a "lapsarian motif" emerges that embodies the fundamental concerns of the Roman moral tradition. Even as it is transposed to different keys and arranged differently in successive authors, the melody remains discernible. For these historians, including Polybius, Sallust, and Livy, the original Roman virtus had become corrupted through a succession of foreign wars, leading to a society morally enervated by a multitude of vices. In contrast to the interpretation of modern historians who attribute the crises of the late Roman Republic to economic and social factors, the ancient historians consistently attribute the problems to a crisis of morality. Drawing on the idea of the longue duree from the Annales school of history, this thesis examines the moral thought of the Roman historical tradition often dismissed by modern historiography. In the process, it argues for a continuity of moral concern in Roman historical thought from Cato the Censor onward, seeking to understand the evolution of the moral tradition expounded by historians of the late Republic, such as Sallust, and assess its continuity with the ethical and historical reflection of the Principate and High Empire periods through the writings of Plutarch.
Keywords: Virtus; Morality; Ethics--Rome--History; Sallust, 86 B.C.-34 B.C; Plutarch; Polybius; Livy; Historians--Rome